2015
DOI: 10.1109/lpt.2015.2414712
|View full text |Cite
|
Sign up to set email alerts
|

Unrepeatered DP-QPSK Transmission Over 352.8 km SMF Using Random DFB Fiber Laser Amplification

Abstract: Abstract-Unrepeatered 100 Gbit/s per channel WDM DP-QPSK transmission with random DFB fibre laser based Raman amplification using fibre Bragg grating is demonstrated. Transmission of 1.4 Tb/s (14 × 100 Gbit/s) was possible in 352.8 km link and 2.2 Tb/s (22 × 100 Gbit/s) was achieved in 327.6 km without employing ROPA or speciality fibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…3(b), the electrical spectra of FW-propagated fiber lasers at 1455 nm are shown. We can see that there was no mode structure, which confirms the laser was operating in the random DFB lasing regime [8][9][10][11]. The reason why the RIN of the signal didn't increase was that the minimized reflectivity near the input end led to the reduced efficiency of the Stokes shift (from second order pump to first order fiber laser) in forward-propagated direction.…”
Section: Experimental Setup and Characterizations Of Different Raman mentioning
confidence: 99%
See 1 more Smart Citation
“…3(b), the electrical spectra of FW-propagated fiber lasers at 1455 nm are shown. We can see that there was no mode structure, which confirms the laser was operating in the random DFB lasing regime [8][9][10][11]. The reason why the RIN of the signal didn't increase was that the minimized reflectivity near the input end led to the reduced efficiency of the Stokes shift (from second order pump to first order fiber laser) in forward-propagated direction.…”
Section: Experimental Setup and Characterizations Of Different Raman mentioning
confidence: 99%
“…The first work on random DFB fiber laser based amplification was demonstrated in [8] where the authors showed a transmission performance improvement using third-order backward pumping. Bidirectional pumping using similar scheme can be also used in unrepeatered transmission in which the RIN-induced penalty on the signal is significantly low [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…300km), the generated Raman fibre laser at 1455nm was no longer a Fabry-Perot fibre laser across the whole cavity/transmission fibre. Instead, it was actually two separate random DFB fibre laser located near each side of the span and had no interaction between each other [10]. Fig.…”
Section: Figure 3 (A)schematic Diagram Of Raman Fibre Laser Based Amentioning
confidence: 99%
“…However, forward-propagated (FW) pumping typically introduces relative intensity noise (RIN) to the signal [4]. Due to the capability of RIN mitigation, second order Raman fibre laser (RFL) based amplification has been proven to be an excellent candidate in both long-haul and unrepeatered transmission [5][6][7][8][9][10]. This paper discusses the key technologies and recent advances in RFL based amplification, which mitigate the RIN penalty and extend the maximum reach in long-haul transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Low noise distributed Raman amplification is now a well-established method that can overcome the limits set by EDFA and satisfy the bandwidth demand. In both long-haul [3,4] and unrepeatered links [5,6], it offers a broader bandwidth of operation [7] and improved noise performance compared to lumped amplification [2]. In particular, higher-order pumping can minimise the signal power variation (SPV) and reduce the effective attenuation by pushing the gain farther into the span [8,9].…”
mentioning
confidence: 99%